A trans‐Selective Hydroboration of Internal Alkynes1. Issue 52 (31st October 2013) - Sundararaju, Basker; Fürstner, Alois
<x xml:space="preserve">Abstract</x> Violate the rule: The reigning stereochemical principle of hydroboration is the suprafacial delivery of hydrogen and boron to the same π‐face of a given starting material. This fundamental rule of cis addition is now easily broken for internal alkynes with the help of [Cp*Ru(MeCN)3]PF6 (Cp*=η5‐C5Me5) as the catalyst. The resulting trans‐selective hydroboration opens a practical new entry into E‐configured alkenylboron derivatives.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>